1980
DOI: 10.1002/cber.19801131208
|View full text |Cite
|
Sign up to set email alerts
|

Lewis‐Säure‐bedingte α‐Alkylierung von Carbonylverbindungen, VII. Regio‐ und positionsspezifische α‐ tert ‐Alkylierung von Ketonen

Abstract: Structurally different ketones can be alkylated at the a-position via their silyl enol ethers with terfalkyl halides in the presence of Lewis acids such as titanium tetrachloride (-27-35). Concerning the alkylation agent, the position specific introduction of branched and cyclic krf-alkyl groups is possible ( 4 4 1 -49). Bridgehead halides of the type 1-adamantyl bromide react analogously ( 4 2 -61). Silyl enol ethers derived from unsymmetrical ketones react regiospecifically (+63, 64, 66, 67). If the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…As illustrated in Scheme 37, using the data of Reetz et al, 160 the more-and less-substituted TMS enol ethers of 2-methylcyclohexanone have been t-butylated with high regiospecificity and in good yields by this method. Paterson has also reported that titanium tetrachloride promoted phenylthioalkylations of the ButCI 1 equiv.…”
Section: Alkylations Via Silyl Enol Ethers and Other Enol Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Scheme 37, using the data of Reetz et al, 160 the more-and less-substituted TMS enol ethers of 2-methylcyclohexanone have been t-butylated with high regiospecificity and in good yields by this method. Paterson has also reported that titanium tetrachloride promoted phenylthioalkylations of the ButCI 1 equiv.…”
Section: Alkylations Via Silyl Enol Ethers and Other Enol Derivativesmentioning
confidence: 99%
“…bislactim ethers such as (159), derived from (S)-valine and glycine or alanine, for the asymmetric synthesis of amino acids. 274 As shown in Scheme 78, compounds such as (159) are deprotonated exclusively at C-5 with n-butyllithium or LDA in THF to give endocyclic chiral enolate equivalents such as (160). Alkylations of (160) with saturated primary, allylic and benzylic halides occur anti to the 2-isopropyl substituent with high diastereoselectivity.…”
Section: Cycloalkylations Of Enolates Of Carboxylic Acid Derivativesmentioning
confidence: 99%
“…For this disconnection, the fully substituted single bond is out of question, as the steric constraints would only cause elimination of the tert-halide precursor but probably no ring closure. This shifts the construction of the quaternary dimethyl-substituted carbon atom to the stage of the halo ketone 13, but for the regio-and position-specific α-tert-alkylation of ketones, Reetz et al [20] had worked out a reliable Lewis acid mediated methodology. Disconnecting the bond between the two highest substituted carbon atoms provides the silyl enol ether of cyclohexanone 14 and 1-bromo-4-chloro-4-methylpentane (15) as building blocks, the latter of which should be accessible by addition of HCl gas to 1a-homoisoprenyl bromide (16).…”
Section: Resultsmentioning
confidence: 99%
“…As summarized in Scheme 4, the addition [21] of HCl gas to 5-bromo-2-methylpent-2-ene (16) in the presence of ZnCl 2 in Et 2 O went smoothly and provided the 1-bromo-ω-chloro building block 15 in 74 % yield. Following the procedure of Reetz et al, [20] cyclohexenyloxy trimethylsilane www.eurjoc.org (14) was then selectively α-alkylated with the tert-substituted chloro side of the bifunctional building block 15 in CH 2 Cl 2 in the presence of titanium tetrachloride as stoichiometric Lewis acid. The resulting 2-(5Ј-bromo-2Ј-methylpentan-2Ј-yl)cyclohexanone (13) was isolated by flash chromatography in 31 % yield and cyclized in the next step in the presence of potassium tert-butoxide in toluene.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenation of 69 to the target structure Scheme 6. This disconnection leads to halo ketone 74, which should be available by a-tert-alkylation of the cyclohexyl silyl enol ether 75 with 1-bromo-4chloro-4-methylpentane (76) according to the methodology of Reetz et al [33]. However, the epimer was odorless, and the correct diastereoisomer 59 was obtained in 71% yield.…”
mentioning
confidence: 99%